2017
DOI: 10.1002/eji.201646565
|View full text |Cite
|
Sign up to set email alerts
|

CD11b regulates the Treg/Th17 balance in murine arthritis via IL‐6

Abstract: Th17 cells are often associated with autoimmunity and been shown to be increased in CD11b mice. Here, we examined the role of CD11b in murine collagen-induced arthritis (CIA). C57BL/6 and CD11b resistant mice were immunized with type II collagen. CD11b mice developed arthritis with early onset, high incidence, and sustained severity compared with C57BL/6 mice. We observed a marked leukocyte infiltration, and histological examinations of the arthritic paws from CD11b mice revealed that the cartilage was destroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…This cell line has already proven to be a reliable model for the study of cDC2s. Indeed, in a recent report from our group, resistance to collagen induced arthritis (CIA) was partially recovered by the adoptive transfer of CD4 − MutuDC2s in a CIA-susceptible CD11b −/− mouse model, highlighting a potential tolerogenic role of cDC2s in the modulation of autoimmune responses (99). Furthermore, the CD4 − MutuDC2s have been successfully transduced with a CRISPR-Cas9 editing system to generate a new CD11b −/− CD4 − MutuDC2 line (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…This cell line has already proven to be a reliable model for the study of cDC2s. Indeed, in a recent report from our group, resistance to collagen induced arthritis (CIA) was partially recovered by the adoptive transfer of CD4 − MutuDC2s in a CIA-susceptible CD11b −/− mouse model, highlighting a potential tolerogenic role of cDC2s in the modulation of autoimmune responses (99). Furthermore, the CD4 − MutuDC2s have been successfully transduced with a CRISPR-Cas9 editing system to generate a new CD11b −/− CD4 − MutuDC2 line (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, LFA-1 is required for the differentiation and suppressive activity of Treg, and its deficiency actually promoted induction of proinflammatory Th17 cells [71,72]. Furthermore, MAC-1 was shown to be required for the induction of peripheral tolerance by suppressing IL-6 secretion and subsequent Th17 differentiation in a model of orally induced tolerance in mouse [255]. Furthermore, MAC-1 maintained autoreactive B cell tolerance by inhibiting B cell receptor signaling [127].…”
Section: Functions Of β2 Integrins In Autoimmunitymentioning
confidence: 92%
“…In a murine collagen-induced arthritis (CIA) model, MAC-1 expression prevented early disease onset, and decreased the severity of CIA via controlling IL-6 secretion and subsequent Th17 polarization of lymphocytes [255]. On C57BL6 genetic background, CD11b −/− mice developed CIA of high severity and incidence, whereas WT mice were fully protected from the disease.…”
Section: Mac-1mentioning
confidence: 99%
“…Accordingly, in this issue, Stevanin et al. observed that in the course of collagen‐induced arthritis, CD11b −/− mice exhibited much higher IL‐6 levels as compared with those of WT control animals. The IL‐6 was produced by DCs and peritoneal macrophages.…”
mentioning
confidence: 98%
“…The report of Stevanin et al. has set the stage for further investigation not only of the biologic role of CD11b (why does CD11b not interfere with murine collagen‐induced arthritis in mice with H‐2 q or H‐2 r MHC haplotypes?) but also of the decisive role of the cytokine IL‐6 in the development of RA and other autoimmune diseases.…”
mentioning
confidence: 99%